High frequency of KRAS and EGFR mutation profiles in BRAF-negative thyroid carcinomas in Indonesia - Heriyanto, Didik Setyo; Laiman, Vincent; Limantara, Nikko Vanda; Anantawikrama, Widyan Putra; Yuliani, Fara Silvia; Cempaka, Rita; Anwar, Sumadi Lukman (BioMed Central Ltd, 2022)
Objective: Thyroid cancer incidence has steadily increased in Indonesia. However, data on Kirsten rat sarcoma virus (KRAS) and EGFR mutations in thyroid cancer in Indonesia remain unavailable, except for BRAF-V600E, the most common BRAF gene mutation. This study aimed to analyze KRAS and EGFR mutation profiles in BRAF-V600E negative thyroid cancer samples. Results: BRAF-V600E mutations were found in papillary thyroid carcinomas in 40.3% patients with mean age of 53 years old. In BRAF-V600E-negative samples, 41.3% had KRAS mutations with mean age of 55.5 years old. KRAS mutation was found in 52.6% of follicular carcinomas and 47.4% of papillary thyroid carcinomas. Additionally, 45.7% had EGFR mutations in patients with mean age of 50.5 years old. EGFR mutation was found in 71.4% of papillary thyroid carcinoma and 28.6% of follicular carcinoma. Nearly half of the BRAF-V600E negative thyroid carcinoma samples harbored either KRAS or EGFR mutations. This finding suggests that in BRAF-V600E negative thyroid carcinoma samples, testing for RAS and EGFR mutation may be warranted for further therapeutic consideration.